Telaah Historis Dan Estetis Dalam Kumpulan Puisi Malu (Aku) Jadi Orang Indonesia Karya Taufiq Ismail - Wawan Wawan (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2019)
This research is entitled "Historical and Aesthetic Study in a Collection of Shame Poems (I) Become Indonesian People by Taufiq Ismail". The background of this research is based on the researchers' interest in poems written by Taufiq Ismail in the period May - November 1998, which has been anologized in the book Malu (I) Becomes an Indonesian (MAJOI). The poems contain events that took place during the final days of Soeharto's rule. Poems in MAJOI are full of historical and sociological anxieties of poets over the situation that occurred during the period May - November 1998. This research was conducted with the aim of answering two main problems, namely: (1) revealing historical values; (2) revealing the aesthetic value of Taufiq Ismail's poems in MAJOI. To be able to answer these two problems an eclectic approach is used, namely an approach which is a combination of several approaches. The several approaches used are structural approaches and stylistic approaches. Because the focus of this research is on the extra-aesthetic study of literary works, the approach first used is the sociological approach to literature. This approach was chosen in relation to historical and aesthetic values. The study of the aesthetic structure of poems by Taufiq Ismail in MAJOI is done by integrating structural and stylistic approaches. From the four poems used as research data, the following conclusions can be obtained (1) Taufiq Ismail's poems contain various social, economic and political problems that occurred during the final days of Soeharto's rule; (2) Themes relating to student movements, poverty, national debt, injustice in the field of law, and corruption are a number of social, economic and political issues expressed by poets with "a style of preaching". Even though he uses a "preaching style," Taufiq Ismail's poems can be enjoyed aesthetically because in expressing his ideas poets use compelling aesthetic means, such as the use of a number of rhymes to achieve euphemism, the use of distinctive language styles and unique typography. Taufiq Ismail's poems in MAJOI not only have power in terms of history, but also have advantages in terms of aesthetics.